Solar Cycle and Long‐Term Trends in the Observed Peak of the Meteor Altitude Distributions by Meteor Radars. Issue 2 (25th January 2023) - Dawkins, E. C. M.; Stober, G.; Janches, D.; Carrillo‐Sánchez, J. D.; Lieberman, R. S.; Jacobi, C.; Moffat‐Griffin, T.; Mitchell, N. J.; Cobbett, N.; Batista, P. P.; Andrioli, V. F.; Buriti, R. A.; et al.
Abstract: The mesosphere/lower thermosphere (MLT, 80–100 km) region is an important boundary between Earth's atmosphere below and space above and may act as a sensitive indicator for anthropogenic climate change. Existing observational and modeling studies have shown the middle atmosphere and the MLT is cooling and contracting because of increasing greenhouse gas emissions. However, trend analyses are highly sensitive to the time periods covered, their length, and the measurement type and methodology used. We present for the first time the linear and 11‐year solar cycle responses in the meteor ablation altitude distributions observed by 12 meteor radars at different locations. Decreasing altitudes were seen at all latitudes (linear trends varying from −10.97 to −817.95 m dec −1 ), and a positive correlation with solar activity was seen for most locations. The divergence of responses at high latitudes indicates an important and complex interplay between atmospheric changes and dynamics at varying time scales. Plain Language Summary: High up in our atmosphere lies the mesosphere/lower thermosphere region (80–100 km); an important transition zone between the atmosphere below and space above. Existing studies indicate that this region is changing (cooling and contracting) in response to increasing greenhouse gas emissions, quite unlike the net warming we see near the surface. However these trend studies are often highly sensitive to choice and length of time period covered, and the methodology and type of measurements used. Here we present for the first time a self‐consistent methodology applied to 12 different meteor radar station datasets located at a diverse range of latitudes. We looked at changes in the mean peak altitude of individual meteoroid detections, and found decreasing peak altitudes at all locations examined (linear trends varying from −10.97 to −817.95 m decade −1 ) consistent with a global cooling and contracting of the upper atmosphere. We also examined the response to the 11‐year solar cycle and found a positive correlation with solar activity (i.e., increased meteoroid peak altitudes during solar maximum, and vice versa) for low and mid‐latitude locations. However we found an anti‐correlation at high latitudes suggestive of an important and complex interplay between atmospheric changes and dynamics at varying time scales. Key Points: Use of geographically diverse meteor radar peak detection altitudes to assess long‐term and 11‐year solar cycle (SC) trends in mesopause region The altitude of observed peak meteor height has decreased over time at all locations, regardless of latitude and data set Positive correlation at low‐ and mid‐latitude locations with the 11‐year SC, but more complex response at high‐latitudes